Successful Guselkumab Treatment in a Patient with Comorbid Psoriasis and Amyotrophic Lateral Sclerosis: A Case Study and Literature Review - Xiong J; Chen X; Huang K; Pan Y (Clinical, Cosmetic and Investigational Dermatology)
Jianxia Xiong, Xiaoli Chen, Kun Huang, Yun Pan Department of Dermatology, The First Affiliated Hospital of Chongqing Medical University, No. 1 Youyi Road, Yuzhong District, Chongqing, 400016, People’s Republic of ChinaCorrespondence: Yun Pan, Email 403518388@qq.comAbstract: Psoriasis is genetically influenced and can be triggered by factors such as infections, stress, and lifestyle. Chronic plaque psoriasis, the most prevalent form, involves key roles for IL-17 and IL-23 in its pathogenesis. Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disorder characterized by the degeneration of motor neurons, resulting in muscle weakness and atrophy. Currently, there is no cure for ALS, and treatment is symptomatic, aimed at improving quality of life. The combination of psoriasis and ALS is relatively rare. Although biologic agents have shown remarkable efficacy in the treatment of chronic plaque psoriasis, we have not found any case reports regarding the use of biologic agents for treating psoriasis accompanied by ALS. Our study presents a patient with severe plaque psoriasis and ALS who exhibited a positive response to Guselkumab, without worsening of ALS symptoms, suggesting a promising therapeutic strategy. This could provide a treatment option for patients with psoriasis combined with ALS.We conducted a comprehensive review of the literature on the comorbidity of neurodegenerative diseases, including Alzheimer’s disease (AD), Parkinson’s disease (PD), multiple sclerosis (MS), and ALS, with plaque psoriasis. This review highlights the differential impact of treatment modalities. Specifically, we found that TNF-α inhibitors may have adverse effects in MS but could provide protective benefits in AD and PD. In ALS patients with psoriasis, IL-17A and IL-23 inhibitors, exemplified by Guselkumab, are suggested as a more suitable alternative due to their lower risk of worsening ALS symptoms.Keywords: biologics, psoriasis, amyotrophic lateral sclerosis, guselkumab, neurodegenerative disorder